Hubungan Disiplin Belajar dan Minat Belajar dengan Hasil Belajar Pendidikan Agama Islam pada Materi Kebebasan Mengemukakan Pendapat Siswa Kelas VII di MTs Negeri 1 Sidoarjo Kabupaten Sidoarjo - Ahmad Ahmad (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2020)
This study aims to determine the relationship of learning discipline and learning interest with learning outcomes of islamic religious education. This study uses a survey method, namely: research conducted on large and small populations, but the data studied is sample data taken from the population, so it is found relative events, distribution, and relationships between sociological and psychological variables ". The following are the results of the study: (1) learning discipline (x1) is positively and strongly correlated with islamic religious education learning outcomes (y) on the subject of freedom of expression in mts negeri 1 sidoarjo sidoarjo regency, with a correlation value of 0.947. (2) interest in learning (x2) is positively and strongly related to learning outcomes of islamic education (y) on the subject of freedom of expression in mts negeri 1 sidoarjo, sidoarjo regency, with a correlation value of 0.935. (3) learning discipline (x1) and learning interest (x2) jointly have a positive and very strong relationship with islamic education learning outcomes (y) on the freedom of expression of material in mts negeri 1 sidoarjo sidoarjo, sidoarjo regency, with a correlation value of 0.951 .